Adverse Events Following Gastrointestinal Endoscopy in Children: Classifications, Characterizations, and Implications. Issue 6 (June 2016) - Kramer, Robert E.; Narkewicz, Michael R.
ABSTRACT: Objective: To conduct a comprehensive study of postendoscopic adverse events (AEs) in children, categorizing them by the level of intervention required. Background: Previous studies of endoscopic AE in children have focused on intraprocedural and short-term outcomes, such as bleeding, perforation, and infection, and may underestimate the incidence of AEs. Design: Prospective observational study tracking AEs in pediatric patients within 72 hours of an endoscopic procedure. Setting: Single-center study performed at an academic, tertiary care, free-standing children's hospital over a 48-month period, from July 2010 through June 2014. Patients and Interventions: Of 9577 pediatric endoscopic procedures, cases identified as having an AE during or following endoscopy were subject to additional chart review for abstraction of relevant data. Main Outcome Measurements: Type, severity, and subsequent interventions of AEs were the primary outcome measures. Events were categorized by severity grade, with grade 1, no intervention; grade 2, outpatient evaluation; grade 3, hospitalization or repeat endoscopy; grade 4, surgery or intensive care unit admission; and grade 5, death. Results: In total, 249 endoscopic AEs were recognized of 9577 procedures performed, yielding a rate of 2.6%. Of these, 160 were identified to result in medical evaluation and costs (≥grade 2) for a rate of 1.7%. Rates of endoscopic AE after advanced or interventional endoscopic procedures were higher, with 65 of 1167 events, resulting in a total AE rate of 5.6% and a rate of 4.4% for AE ≥ grade 2. There were 10 cases of significant bleeding (0.1%), 9 cases of infection (0.09%), and 12 cases of perforation (0.13%), primarily occurring with advanced/interventional procedures. Limitations: Single-center study, lack of standardized criteria for ED referral. Conclusions: AEs presenting within 72 hours of endoscopy and resulting in medical intervention, occur more commonly than previously recognized in children. Standardized postendoscopy surveillance systems and definitions of AEs are needed.